KEADAAN JALAN HUTAN DI HUTAN JATI DAN POTENSINYA DALAM AKSELERASI EROSI TANAH - DJaban Tinambunan (Pusat Penelitian dan Pengembangan Hasil Hutan, 1991)
An inuestigation on forest road conditiona in teak forests of Cepu and Randublatung Forest Districts and their soil erosion potentials was conductild in early 1991. The samples of roads inuestigated were 30 segments in Cepu and 14 segments in Randublatung each of 60 m long.It is found that from the total of 266 km truck roads in Cepu, only 3.7% of them are in 2% are active roads. for the 180 km rail roads, 65.4% are in good conditionsIn Randublatung. the total length of truck roads is 237 km of which only 11.8% are in good conditiouns but 78.3% are active roads For rail roads, the total length is only 33 km and only 13.5% of them are in good conditionsThe total area used for road infrastructures (combined truck and rail roads) in cepu and Randublatung are 266 ha (0;8%) and 163 ha (8.5%), respectively. This means that an average land lost due to roading is 0. 7%.All factors in the USLE for the teak forest areas of Cepu and Randublatung are in the level of low scores in terms of soil erosion acceleration potentials except soil erodibility. It is noticed in the field that this soil erodibility factor is couered by other dominant facton and. therefore, soil erosion potentials of forest roads roads are generally low.